An immunomodulatory polysaccharide from blackberry seeds and its action on RAW 264.7 cells via activation of NF-κB/MAPK pathways. Issue 1 (1st January 2020) - Wang, Junya; Zhang, Hongli; Wang, Honglin; Wang, Jinmei; Sun-Waterhouse, Dongxiao; Waterhouse, Geoffrey Ivan Neil; Ma, Changyang; Kang, Wenyi
ABSTRACT: Currently there is tremendous interest in the discovery of natural polysaccharide immunomodulators for treating immune-related diseases. Herein, the immunomodulatory activities of a polysaccharide fraction isolated from blackberry seeds (BSP-2) were examined in RAW264.7 cells. The results revealed that BSP-2 at 37.5–300 µg/mL could significantly enhance the phagocytic activity of RAW264.7 cells and their ability to release NO, TNF-α and IL-6 cytokines. BSP-2 could significantly up-regulate the mRNA expression of iNOS, TNF-α and IL-6, as well as the phosphorylation of p65, p38, ERK and JNK proteins. The mechanisms underlying the immunomodulatory actions of BSP-2 likely involve the activation of the NF-κB and MAPK signaling pathways and up-regulation of the phosphorylation of key proteins involved in these pathways. These findings suggest that BSP-2 could be applied as a polysaccharide immunotherapeutic adjuvant with the effective dose as low as 70 µg/mL (BSP-2 may be cytotoxic at levels > 600 μg/mL). Highlights Immunostimulatory potential of a blackberry seed polysaccharide (BSP-2) was examined. BSP-2 at 37.5–300 µg/mL could enhance the phagocytic activity of RAW264.7 cells. BSP-2 could significantly up-regulate the mRNA expression of iNOS, TNF-α and IL-6. BSP-2 up-regulated the phosphorylation of p65, p38, ERK and JNK proteins. Immunostimulatory BSP-2 acted via activating the NF-κB and MAPK signalling pathways.